The learning process: key phases and elements - Yánez-Moretta, Patricio; Betty Loaiza-Ramírez, (Seven Editora, 2023)
This article is a commented analysis that seeks to present, point out, and discuss the main features of the stages of the learning process that occurs gradually in an interconnected way: motivation, interest, attention, acquisition, understanding, assimilation, application, transference, and evaluation. It presents some own arguments, as well as others at every stage. The document is particularly aimed at those who in one way or another perform everyday teaching activities at different educational levels.DOI: https://doi.org/10.56238/devopinterscie-061